Long-term effectiveness of non-surgical open-bite treatment: a systematic review and meta-analysis - Maria-Zoi Theodoridou; Athanasia-Eirini Zarkadi; Vasileios F. Zymperdikas; Moschos A. Papadopoulos (SpringerOpen, 2023)
Abstract Background The etiology of open bite is complex, involving various genetic or environmental factors. Several treatment alternatives have been suggested for the correction of open bite, yet their long-term effectiveness remains controversial. Objective To assess the long-term effectiveness of open-bite treatment in treated with non-surgical approaches versus untreated patients, through lateral cephalometric radiographs. Search methods Unrestricted search of 16 electronic databases and manual searches up to November 2022. Selection criteria Randomized or non-randomized controlled trials reporting on the long-term effects of open-bite treatment through angular lateral cephalometric variables. Data collection and analysis Only angular variables on lateral cephalometric radiographs were considered as primary outcomes. For each outcome, the mean differences and 95% confidence intervals were calculated using the random-effects model to consider existing heterogeneity. The revised Cochrane risk-of-bias tool (R.o.B. 2.0) and the risk-of-bias tool for non-randomized studies for interventions (ROBINS-I) were utilized for the randomized and non-randomized trials, respectively. Results From the initially identified 26,527 hits, only 6 studies (1 randomized and 5 retrospective controlled trials) were finally included in this systematic review reporting on 244 open-bite individuals (134 patients and 110 untreated controls), while five of them were included in the meta-analyses, assessing either the interval ranging from treatment start to post-retention (T3-T1) or from end of treatment to post-retention period (T3-T2). Regarding the vertical plane, for the T3-T2 interval, no significant differences were found for the assessed skeletal measurements, indicating a relative stability of the treatment results. Similarly, with regard to the T3-T1 interval, no significant differences could be identified for the examined skeletal variables, implying that the produced effects are rather minimal and that the correction of the open bite was performed mainly through dentoalveolar rather than skeletal changes. Further, no significant changes could be identified regarding the inclination of the upper and lower incisors. Only the nasolabial angle was significantly reduced in the treated patients in the long term. Conclusions According to existing evidence, the influence of non-surgical treatment of open bite on the skeletal tissues and the inclination of the incisors is rather minimal in the long term, while only the nasolabial angle was significantly reduced.